Perlindungan Hukum Bagi Tenaga Kerja Perempuan di Bidang Usaha Kegiatan Konstruksi - Hari Sapto Adji; Abdul Rahmat (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2023)
Development is a planned effort that is carried out consciously by a developing country. This also happened in the country of Indonesia which also carried out development called National Development. Regarding the implementation of national development, the position and role of the workforce is very important as an actor and goal of development. Manpower development must be regulated in such a way as to fulfill basic rights and protection for workers. And at least at the same time creating conducive conditions for the development of the business world. Manpower development has many dimensions and interrelationships not only with the interests of the workforce during, before and after the working period but also related to the interests of employers, government and society. For this reason, comprehensive and comprehensive arrangements are needed, which include developing human resources, increasing labor productivity and competitiveness, efforts to expand employment opportunities, manpower placement services, and fostering industrial relations which also apply in the construction business sector. The entry of women into the world of work will automatically lead to a working relationship. The working relationship itself occurs after the existence of a work agreement between workers and employers. With this agreement, there will be rights and obligations bound therein. The protection in question is the protection of safety, health, decency, maintenance of work morale and treatment in accordance with human dignity and religious morals.